2017
DOI: 10.1093/europace/eux211
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial left atrial appendage AtriClip occlusion reduces the incidence of stroke in patients with atrial fibrillation undergoing cardiac surgery

Abstract: URL: http://www.clinicaltrials.gov. Unique identifier: NCT00567515.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 41 publications
1
76
0
2
Order By: Relevance
“…Initial results from a prospective European clinical pilot trial and a US-based multicenter trial (EXCLUDE) showed a good safety and efficacy profile for the AtriClip device using systematic imaging in controlled follow-up at 3 months [7,14]. These data were further validated by computed tomography in controlled mid-and long-term studies demonstrating safe, durable and complete LAA occlusion [9,15,16], as well as initial signs of potential reduction of stroke risk in patients with discontinued OAC [8]. A recent systematic review on outcomes of LAA occlusion using the AtriClip device showed the device to be safe and effective in the management of patients with atrial fibrillation, either as an adjunct in patients undergoing cardiac surgery or as a stand-alone thoracoscopic procedure with successful LAA occlusion in 97.8% of patients and no reported device-related adverse events [17].…”
Section: Evidence Of Epicardial Device Enabled Laaomentioning
confidence: 94%
See 2 more Smart Citations
“…Initial results from a prospective European clinical pilot trial and a US-based multicenter trial (EXCLUDE) showed a good safety and efficacy profile for the AtriClip device using systematic imaging in controlled follow-up at 3 months [7,14]. These data were further validated by computed tomography in controlled mid-and long-term studies demonstrating safe, durable and complete LAA occlusion [9,15,16], as well as initial signs of potential reduction of stroke risk in patients with discontinued OAC [8]. A recent systematic review on outcomes of LAA occlusion using the AtriClip device showed the device to be safe and effective in the management of patients with atrial fibrillation, either as an adjunct in patients undergoing cardiac surgery or as a stand-alone thoracoscopic procedure with successful LAA occlusion in 97.8% of patients and no reported device-related adverse events [17].…”
Section: Evidence Of Epicardial Device Enabled Laaomentioning
confidence: 94%
“…In particular, durability and completeness of LAA closure still represent major issues for most surgical approaches, thus limiting the overall therapy efficacy [4]. In this regard, device-enabled epicardial approaches have been repeatedly suggested as a potential option to achieve safe, complete and durable occlusion of the LAA [8]. Notably, 10 years after its introduction and with currently > 200.000 devices sold, the AtriClip device possesses the largest body of clinical experience for device-enabled surgical approaches.…”
Section: Evidence Of Epicardial Device Enabled Laaomentioning
confidence: 99%
See 1 more Smart Citation
“…The AtriCure LAA Exclusion system, a nitinol-based clip surrounded by a cotton scarf, was invented to securely close the LAA at the base with equal force distribution over the complete length of the clip. This device was introduced for use with concomitant cardiac surgery in 2007 with very good results in the short term as well as in the long-term followup period [41][42][43][44][45]. Suwalski et al [46], in a subsequent transoesophageal echocardiography study, showed that successful closure of the LAA during off-pump heart surgery with the AtriClip LAA exclusion system was possible in all patients studied, irrespective of the anatomy of the LAA.…”
Section: Surgical Treatment Options For the Left Atrial Appendagementioning
confidence: 98%
“…Многие авторы указывают на высокую эффективность устройства AtriСlip в отношении полноты окклюзии и его безопасность при использовании как на открытом сердце [30,31], так и торакоскопически [32,33]. Расширяется доказательная база относительно эффективности приспособления AtriClip в профилактике инсульта у пациентов с высоким риском по шкале CHA 2 DS 2 -VASс [34]. Однако необходимо отметить высокую стоимость устройства, наличие выступающих частей, которые потенциально могут травмировать окружающие ткани, а также пружинный механизм закрытия браншей клипсы, который неизбежно приводит к очагам микронекрозов в зоне сжатия.…”
Section: The Foregoing Has Determined High Level Of Interest In Creatunclassified